Periodikos pradžia Lietuvoje - Petrauskienė, Irena (Knygotyra, 1974)
The periodicals in the Grand Duchy of Lithuania emerged as a product of the expanding ties among the countries and the arising need for information. In the history of periodicals in Lithuania as also in other countries there have been two clearly distinguishable stages: first – publishing of calendars and the later of newspapers. As an initiator in this field appears the printing press of the Academy of Vilnius.From 1737 (according 10 autobiographic data even from 1735) till 1741 calendars were published by I. Poshakovskis, from 1758 – by F. Paprockis. They both cardinally changed the contents of the calendars, rejecting the accepted at that time prognostics and even ridiculing them. Calendars received by them a topical historical-political character. Besides the usual calendar information, the editors inserted bits of astronomical, historical, geographical information and news about various events. In addition to that F. Paprockis published scientific papers, official documents, enactments of the parliament (sseim). The calendars paved the way to the newspapers, fostered the reading habits and the need for a more operative information.At the beginning of 1760 (19th of April) there appeared the first issue of the first newspaper “The Lithuanian Courier” (Kuryer Litewski) and “The Literary Records” (Wiadomości literackie), and a year later – “The Gazette of Vilnius” (Gazety Wilenskie). Besides these 1760–1763 there were published as supplements to them: “The Foreign New” (Wiadomosci cudzoziemskie) and from 1761 “The Supplements to the Gazette of Vilnius” (Supplement do Gazet Wilenskich). From 1764 were published only the “Gazette of Vilnius” and the supplements to it, which were published also after closing in Lithuania of the Jesuite Order.The newspapers were a new type of the literary production, they attracted readers by their periodic character ant the freshness of information they contained. Much space in them occupied foreign news, but some place has been allotted to the local materials, which are now of great help by the restoring the historic background of those times, by fixing the events happened in the country and is therefore of a considerable cognitive value. Through articles on various fields of knowledge the newspapers of the Academy deserve a high appraisal as popularizers of scientific knowledge. The ideological trend of these periodicals was determined by the interests of the Jesuite Order and the ruling circles of the society.